The Underreported Postoperative Suffering after Thyroid Surgery: Dysphagia, Dysphonia, and Neck Pain—A Cross-Sectional Study - Hunduma Jisha Chawaka; Zenebe Bekele Teshome (Anesthesiology Research and Practice)
Background and Aims. Postoperative voice change, difficulty of swallowing, throat pain, and neck pain are the most commonly complaint after thyroid surgery. However, little emphasis is given to the problem, especially a place where the surgical and anesthesia services’ unmet need is highly observed, i.e., the problem gets little attention especially in the countries where the gaps of surgery and anesthesia services are observed. Hence, this study aims to determine the magnitude and associated factors of voice change and related complaints after thyroid surgery. Methods. A cross-sectional study was conducted on 151 patients who had had thyroid surgery from June 1 to December 30, 2021. Data were retrieved during the postoperative period after the patient regains consciousness. Result. Out of 151 participants, 98 (64.9%) patients complained of either voice change or difficulty of swallowing and neck pain after thyroid surgery within 24 hours. Majority (58.3%) of the participants aged more than 30 years with a mean age of 33.7 ± 8.3 years and females 102 (67.5%). Neck pain is the most (52.3%) complained suffering after thyroid surgery, followed by voice change 38.4% and difficulty in swallowing 37.7%. Difficulty in swallowing after thyroid surgery significantly associated with a patient who frequently experience intraoperative hypotension (AOR = 23.24, 95% CI 4.6–116.7, and p=0.01), type of surgical procedure (total thyroidectomy) (AOR = 8.62, 95% CI 1.21–61.50, and p=0.03), and larger ETT size (AOR = 4.92, 95% CI 1.34–18.01, and p=0.02). Postoperative voice change is associated with larger endotracheal tube (AOR = 15.47, 95% CI 3.4–69.5, and p≤0.001), surgery lasting more than 2 hours (AOR = 7.34, 95% CI 1.5–35.1, and p=0.01), and intraoperative hypotension (AOR = 23.24, 95% CI 4.6–116.7, and p≤0.001). Conclusion. The complaint of postthyroidectomy neck pain and throat discomfort is higher than 64.9%. Intraoperative hypotension, blood loss, higher ETT size utilization, and duration of surgical procedure are the identified possible risk factors and have to be minimized as much as possible. Patient reassurance has to be considered during the postoperative time.